Summary of best evidence for safe management of vasopressors through peripheral intravenous catheters - Guanjie Chen; Chen Shen; Chenwei Pan; Xiaohui Gao; Mingzhu Sun; Xiaoqing Li (BMC Nursing)
Abstract Background Vasopressors are critical for maintaining hemodynamic stability in critically ill patients, traditionally administered via central venous catheters (CVCs). However, CVCs carry risks of complications and insertion delays. Peripheral intravenous catheters (PIVCs) offer a rapid alternative but pose risks of extravasation and phlebitis. This study aimed to evaluate and summarize the evidence for the safe management of vasopressors through peripheral intravenous catheters, providing reference for clinical practice. Methods This evidence summary utilized the standard evidence summary report of Fudan University Center for Evidence-based Nursing, which includes problem establishment, evidence retrieval, literature screening, quality evaluation of the literature, the summary and grading of evidence. The registration number is “ES20246694”. Current literatures were systematically searched for the best evidence for safe management of vasopressors through PIVCs. BMJ Best Practice, UpToDate, DynaMed, Joanna Briggs Institute, Cochrane Library, Guidelines International Network, National Institute for Health and Clinical Excellence, Scottish Intercollegiate Guidelines Network, Registered Nurses’ Association of Ontario, Intravenous Nurses Society, Chinese Nursing Association, PubMed, Embase, CINHAL, Web of Science, Chinese Medical Journal Full-text Database, Sinomed, CNKI, Wanfang, and VIP were searched from database establishment to 27 June 2025. Literature types included clinical practice guidelines, clinical decisions, expert consensuses, systematic reviews, and evidence summaries. Results Our systematic search retrieved 1,925 publications, and finally identified 12 articles that had high-quality results. The evidence synthesis comprised three clinical decisions, four guidelines, one expert consensus, and four systematic reviews. We summarized the 29 pieces of best evidence from these articles, covering five aspects: training and education, infusion site selection, vascular access placement, infusion regimen optimization, and complication management. Of these pieces of evidence, 23 were ‘strong’ and 6 were ‘weak’, 9 pieces of evidence were recommended in level one. Conclusion The following 29 pieces of evidence for safe management of vasopressors through peripheral intravenous catheters were finally recommended. However, due to the multinational origin of the evidence, feasibility, appropriateness, clinical significance, and effectiveness must be evaluated within institutional contexts prior to implementation.